Intra- and inter-individual variability of Aspergillus fumigatus reactive T-cell frequencies in healthy volunteers in dependency of mould exposure in residential and working environment - Wurster, Sebastian; Weis, Philipp; Page, Lukas; Helm, Johanna; Lazariotou, Maria; Einsele, Hermann; Ullmann, Andrew J. (Mycoses, 2017)
Invasive aspergillosis remains a deadly disease in immunocompromised patients, whereas the combination of an exaggerated immune response and continuous exposure lead to various hyperinflammatory diseases. This pilot study aimed to gain an overview of the intra- and inter-individual variability in Aspergillus fumigatus reactive T-helper cells in healthy adults and the correlation with environmental mould exposure. In this flow cytometric study, the frequencies of CD154+ A. fumigatus reactive T cells were evaluated in 70 healthy volunteers. All subjects completed a standardised questionnaire addressing their mould exposure. Subjects with intensive mould exposure in their professional or residential surrounding demonstrated considerably higher mean frequencies of A. fumigatus reactive T-helper and T-memory cells. Comparative evaluation of multiple measurements over time demonstrated relatively conserved reactive T-cell frequencies in the absence of major changes to the exposure profile, whereas those frequently exposed in professional environment or with changes to their risk score demonstrated a marked dependency of antigen reactive T-cell frequencies on recent mould exposure. This pilot study was the first to provide data on the intra-individual variability in A. fumigatus reactive T-cell frequencies and its linkage to mould encounter. Fungus reactive T cells are to be considered a valued tool for the assessment of environmental mould exposure.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Aspergillus; biomarker; CD154; flow cytometry; mould exposure; T cells